1983
DOI: 10.1159/000469599
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Liver and Kidney Adenine Nucleotide Translocase and Pyruvate Dehydrogenase Activity to Alloxan Diabetes

Abstract: Adenine nucleotide translocase (EC 3.6.1.3.), pyruvate dehydrogenase (active and total forms, EC 1.2.4.1) and the long chain acyl CoA content were measured in liver and kidney from normal and alloxan-diabetic rats. The long chain acyl CoA content was significantly increased in liver, but not in kidney, in the diabetic group. Adenine nucleotide translocase activity was decreased in liver and raised in the kidney of alloxan-diabetic rats relative to the control group. Pyruvate dehydrogenase (active) was inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…It has been reported that the pyruvate dehydrogenase activity in the liver decreases significantly in diabetes [8,13]. Also, treatment with insulin did not reverse the changes in the respiration rates.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…It has been reported that the pyruvate dehydrogenase activity in the liver decreases significantly in diabetes [8,13]. Also, treatment with insulin did not reverse the changes in the respiration rates.…”
Section: Discussionmentioning
confidence: 85%
“…Considerable amount of work has been carried out to evaluate the effect of diabetic state and insulin treatment on oxidative energy metabolism in the liver mitochondria (e.g. Surprisingly, however, hardly any work has been carried out along these lines to examine the energy-linked functions of the kidney mitochondria in diabetic state or following insulin treatment [8,20]. Surprisingly, however, hardly any work has been carried out along these lines to examine the energy-linked functions of the kidney mitochondria in diabetic state or following insulin treatment [8,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations